THE PRINCIPLE OF ULTIMUM REMEDIUM IN CRIMINAL TAX MATTERS - Jadidah, Fikrotul (IBLAM LAW REVIEW, 2023)
This research examines various aspects related to tax violations in Indonesia, focusing on the legal regulations governing tax violations, corporate accountability in tax criminal actions, and the use of criminal sanctions as the ultimum remedium. This research employs a normative legal research method, referring to secondary data sources consisting of relevant primary and secondary legal materials. The findings of this study conclude that tax violations can be categorized into two groups, namely negligence and intentional violations, corporations can be held criminally accountable in cases of tax violations, and criminal sanctions in taxation are considered a last resort in tax enforcement. As recommendations, this research proposes the development of a tax amnesty policy, increased tax education and awareness, as well as regular audits and enhanced transparency in tax reporting as efforts to ensure better tax compliance.